An investigation on tensile, compression and flexural properties of natural fibre reinforced polyester composites - B. F., Yousif; K. J., Wong; N. S. M., El-Tayeb (2007)
In the present work, effects of two types of natural fibres on mechanical properties of polyester composites were investigated at different volume fractions of fibre. Tensile, compression, and flexural properties of oil palm bunch and oil palm fruit fibres reinforced polyester composites were investigated. Additionally, tensile strength of the selected composites was calculated theoretically. Scanning electron microscope was used to observe the fracture mechanism of the specimens. Single fiber pull-out tests were carried out to determine the interfacial shear strength between polyester resin and both types of oil palm fibre. As results, it was found that both types of oil palm fibre enhanced the mechanical performance of polyester composites. At higher volume fraction (approximate to 41%), tensile strength was improved, when polyester reinforced with oil palm fruit fibres, i.e. 2.5 folds improvement in the tensile strength value. Further, experimental tensile strength values of oil palm bunch/polyester composites was found to be less varied compared to theoretical results. Flexural strength of polyester was worsened with oil palm fibres at all of fibre volume fraction.